PEMANFAATAN TANAMAN HERBAL SEBAGAI OBAT TRADISIONAL UNTUK KESEHATAN MASYARAKAT DI DESA GUAAN KECAMATAN MOOAT KABUPATEN BOLAANG MONGONDOW TIMUR - Grenvilco D. Kumontoy (HOLISTIK, Journal of Social and Culture, 2023)
Herbal plants are plants that have been identified and known based on human observations to have compounds that are beneficial for preventing, curing diseases, performing certain biological functions. Understanding traditional medicinal plants is also often called a living pharmacy, which is the use of part of the land so that it can be planted with medicinal plants that are used for daily purposes. As we know, the drug itself is classified into two types, the first chemical drug, the next traditional herbal medicine. Chemical drugs are drugs from the results of chemicals, the material is obtained from synthetics on a large scale and can be used by the public after research from experts first. While herbal medicine is a medicine from the results of plant extracts based on what the community has experienced about the use of these plants has succeeded in reducing or curing diseases that have currently been done research by experts on what substances are contained in it and the efficacy of these substances. Since a long time ago, parents in Guaan Village often use traditional medicines whose ingredients are deliberately planted in the garden and around the house, one of which is ginger (Zingiber officinale) to cure coughs, some even grow wild, which people usually call laka flowers (Impetiens balsamina L) for wound healing. However, currently only certain people, especially the elderly, are still preserving the tradition, so it is feared that the existence of traditional medicine and its use will gradually become extinct. Keywords: utilizer, herbal medicine, traditional